ALANA RIVER BASIN MANAGEMENT - Sharef, Arkhawan Jawhar; Dara, Rebwar Nasir; Ahmed, Ali Rashid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The main aim of this study is to highlight how the Alana River Basin (ARB) will meet future water needs and optimal monthly water distribution policies. The Water Evaluation and Planning System (WEAP) model was applied in order to determine the ARB and the operation plan policy using data for the past 16 years (2000-2015). The model result determined that the current regulations and practices regarding water use and pollution patterns are inadequate. An ideal scheme has been developed and implemented for various scenarios such as domestic water needs, irrigation water, and tourism. Four scenarios have been considered in this study, which are basic scenarios, a higher population growth scenario, a severe flow requirements scenario, and a scenario of adding dams. Comparisons show that the demand for water from April to September is high due to the agriculture season and the high temperature. The maximum demand for water is 3 million cubic meters, which occurs in August, while the proposed dam provides only 2 million cubic meters. In addition, the maximum demand for domestic water is 0.4733 MCM and the minimum is 0.36978 MCM, which is roughly the same level of water demand for every month. Accordingly, the government should start supplementing the Gali Bale dam. However, it is not a sufficient dam to cover the water demand, so the construction of additional dams is strongly suggested.